Sylvia and Bird - Rayner, Catherine (London : Little Tiger Press, 2010)
Sylvia, a dragon, overcomes her loneliness and finds a true friend in Bird.
2.8
K-3
Keywords: Birds -- Juvenile fiction; Dragons -- Juvenile fiction; Friendship -- Juvenile fiction; Loneliness -- Juvenile fiction; Birds -- Fiction; Dragons -- Fiction; Friendship -- Fiction; Loneliness -- Fiction; Birds -- Fiction; Dragons -- Fiction; Friendship -- Fiction; Loneliness -- Fiction